The Effect of Training Based on James Brown Model on Self-efficacy in Adolescents with Type 1 Diabetes Mellitus - Zahra Yosefi; Mohammad Afshar; Neda Mirbagher Ajorpaz; Zohre Sadat (Journal of Holistic Nursing and Midwifery)
Introduction: Type 1 Diabetes Mellitus (T1DM) is one of the most frequent chronic diseases among children and adolescents. Educational strategies underscore patient’s roles in the management of diseases and enhance self-efficacy behaviors. Objective: The purpose of this study was to investigate the effects of an educational intervention based on James Brown’s model on self-efficacy in adolescents with T1DM. Materials and Methods: In this randomized clinical trial, 70 participants were selected and assigned to the control and intervention groups by random block. The two groups received routine care for T1DM. The intervention group was also provided with educational sessions, 60 minutes twice a week for 4 weeks, based on the educational model. The participants completed the diabetes management self-efficacy instrument at the beginning, at the end, and a month after the end of the study. Data analysis was performed using the Chi-square, Independent samples t-test, Covariance (ANCOVA), and repeated measures ANOVA. Results: The mean±SD age of the intervention and control groups was 14.81±2.05 and 15.18±2.11 years, respectively. Before the intervention, the two groups were not different statistically in terms of demographic variables (age, sex, duration of diabetes, insulin intake, etc.) and self-efficacy. The results showed that immediately after the intervention and also in the follow-up stage, the mean scores of self-efficacies and its subscales (nutrition, blood glucose monitoring, physical activity, and medical treatment) in the intervention group were significantly higher than the control group (P<0.05). The mean scores of self-efficacies at the beginning, at the end, and a month after the end of the study were 27.97±5.08, 41.46±4.41, and 44.55±4.38, respectively. In the control group, however, these differences were not significant. Conclusion: The education based on James Brown’s model can improve self-efficacy among adolescents with T1DM. It is recommended that nurses use this method to increase self-efficacy in adolescents with T1DM.